2018
DOI: 10.1007/s10963-018-9118-y
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to Interpreting Mesolithic Mobility and Settlement in Britain and Ireland

Abstract: The Mesolithic communities of northwest Europe have generally been considered inherently mobile, and all the material evidence associated with them has been interpreted accordingly. This has resulted in entrenched, theoretically polemical and largely hypothetical mobility models, focusing on seasonal rounds and extraction activities. However, recent reanalyses of the ethnographic sources, and discoveries of both substantial and ephemeral Mesolithic structures, as well as new data from recent innovative lithic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Bronze Age sites are more diverse, including burial monuments, metalwork, pottery, circular enclosures and rock art, indicating a significant occupation of the landscape. Late Mesolithic sites (Barnes, 1982; Wymer, 1977) are abundant at altitude (Figure 1, Section B), and Rishworth Moor lies within the main Pennine distribution area for Late Mesolithic flint microliths (Keighley, 1981; Preston, 2013a, 2013b; Preston and Kador, 2018; Radley et al, 1974; Spikins, 1999; Stonehouse, 1987; Switsur and Jacobi, 1975; Wymer, 1977). These flint scatters were temporary hunting camps within a larger hunter-gatherer territory (Preston, 2013a, 2013b).…”
Section: Methodsmentioning
confidence: 99%
“…Bronze Age sites are more diverse, including burial monuments, metalwork, pottery, circular enclosures and rock art, indicating a significant occupation of the landscape. Late Mesolithic sites (Barnes, 1982; Wymer, 1977) are abundant at altitude (Figure 1, Section B), and Rishworth Moor lies within the main Pennine distribution area for Late Mesolithic flint microliths (Keighley, 1981; Preston, 2013a, 2013b; Preston and Kador, 2018; Radley et al, 1974; Spikins, 1999; Stonehouse, 1987; Switsur and Jacobi, 1975; Wymer, 1977). These flint scatters were temporary hunting camps within a larger hunter-gatherer territory (Preston, 2013a, 2013b).…”
Section: Methodsmentioning
confidence: 99%
“…It has sometimes been suggested that the later Mesolithic communities of Britain were not only isolated, but sparsely distributed and culturally impoverished (see, for example, Miles 2016). In all probability there was considerable variation in patterns of settlement, mobility and subsistence during this period (Preston & Kador 2018), although a picture of very numerous small sites that had been repeatedly returned to is quite widespread throughout much of Britain, in a variety of different environments (Champness 2014; Simmonds et al 2019, 52; Waughman 2017, 12; Wickham-Jones et al 2020). However, there are also sites like Stainton West in Cumbria (Brown 2021) and Blick Mead in Wiltshire (Jacques & Phillips 2014, 24), which attest dense accumulations of population and appreciable logistical sophistication.…”
Section: Timing and Continuitymentioning
confidence: 99%
“…Conventionally, archaeological understandings of hunter-gatherer mobility hinge on fixed, cyclical patterns of annual movement (the seasonal round), and dichotomies between either the regular movement of ‘base camps’, or task-specific mobility, which ‘maps on’ to natural resources (residential/logistical mobility). These have been soundly critiqued within both anthropology and studies of the British and Irish Mesolithic (Kelly 1995; Spikins 2000; Preston & Kador 2018). The only robust case study on late fifth-millennium cal BC mobility in Britain comes from Oronsay, in the Inner Hebrides.…”
Section: Propositionmentioning
confidence: 99%